Oppression and Violent Resistance of David Martinez and Its Impact in Cyberpunk: Edgerunners Towards Arasaka - William Jason Budiman; Liliek Soelistyo (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This thesis explores how oppression and violent resistance are portrayed in the anime Cyberpunk: Edgerunners through the character of David Martinez. Using Iris Marion Young's "Five Faces of Oppression" and Frantz Fanon's theory of violent resistance is used for the analysis of how the oppressive conditions imposed by Arasaka Corporation lead David to walk the path of violent resistance as a means to reclaim his humanity and agency. I examine how David's story illuminates the dynamics of violent oppression and resistance. Analysis of David's character serves as a lens through which to examine the dynamics of oppression and resistance, explaining how his violent resistance not only breaks him from oppression but also inspires others to challenge oppression. The analysis finds four types of oppression that happen to David which are marginalization, victim of violence, cultural imperialism, and powerlessness. These oppressive conditions lead to two effects of David’s resistance which is David’s death and the rebirth of humanization.